2021
DOI: 10.1039/d1cp00835h
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic model of thin-film fluorescent sensors for strategies to enhance chemical selectivity

Abstract: An analytical model was developed for thin film chemical sensors which provides insight into the sensor dynamics and potential strategies to develop chemical recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Excitation of the films was performed using 405 nm continuous wave laser light from a diode laser (Photonic Solutions) after attenuation of the power to 16 µW. Photoluminescence from the sensors was measured using a fibre-coupled CCD spectrometer, taking a measurement every 3 s for 300 s. Explosives vapours were generated using the setup as shown in [21] and nitrogen was used as the carrier gas, and at a flow rate of 6 mL/min. To check for fluorescence recovery, nitrogen gas was used to flush the analyte-exposed sensors, or the sensors heated to 90 • C, followed by a flow of nitrogen gas to flush out the desorbed analytes from the chamber.…”
Section: Explosives Vapours Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Excitation of the films was performed using 405 nm continuous wave laser light from a diode laser (Photonic Solutions) after attenuation of the power to 16 µW. Photoluminescence from the sensors was measured using a fibre-coupled CCD spectrometer, taking a measurement every 3 s for 300 s. Explosives vapours were generated using the setup as shown in [21] and nitrogen was used as the carrier gas, and at a flow rate of 6 mL/min. To check for fluorescence recovery, nitrogen gas was used to flush the analyte-exposed sensors, or the sensors heated to 90 • C, followed by a flow of nitrogen gas to flush out the desorbed analytes from the chamber.…”
Section: Explosives Vapours Sensingmentioning
confidence: 99%
“…An investigation of the complex processes during the temperature ramp is in progress. Although the source of the DNT vapour was turned off and the system flushed with clean nitrogen, the fluorescence continued to decrease, suggesting that there was a continuing diffusion of DNT vapour into the film [14,21] and that there was a strong binding interaction between the DNT molecules and the SY film [17]. An increase in temperature can weaken the binding strength and release the DNT molecules from the thin film.…”
Section: Fluorescence Quenching and Thermal Release Of Dnt From Sensorsmentioning
confidence: 99%
“…The responses from the various array elements give a fingerprint unique to a particular analyte. 12,13 Recently, Campbell and Turnbull 14 presented some computational and experimental results studying the interactions of explosives molecules with fluorescent films of various thicknesses. They suggested that analysis should make use of fluorescence recovery after a chemical incident instead of fluorescent quenching because this could give better information about the sensor(s)/analyte(s) interactions, thereby discriminating between analytes.…”
Section: Introductionmentioning
confidence: 99%
“…The irreversible interaction has been attributed to a strong binding interaction between the thin film of the sensors and the analytes. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, for xLSCO, wider applications in the energy and sensor fields of the present materials in the thin films field have also been reported in recent years. They are suitable for interconnect materials in solid oxide fuel cells [23][24][25], transparent electrolytes and electrodes of batteries and generators [26][27][28][29][30], thin-film fluorescent sensors, and high-temperature sensing [17,18,31,32], with their high melting point of 2490 • C, good conductivity, and high Seebeck coefficient. From our previous work [17], a screen-printed thick-film thermocouple fabricated by LaCrO 3 (LCO) and La 0.8 Sr 0.2 CrO 3 can be used to measure a temperature of 1550 • C for 10 h in air, which has inspired the fabrication of TFTCs by using xLSCO electrodes.…”
Section: Introductionmentioning
confidence: 99%